The hard road to data interpretation: 3 or 6 months of adjuvant chemotherapy for patients with stage III colon cancer?. (9th February 2018) - Sobrero, A; Grothey, A; Iveson, T; Labianca, R; Yoshino, T; Taieb, J; Maughan, T; Buyse, M; André, T; Meyerhardt, J; Shields, A F; Souglakos, I; et al.
Abstract: Background: Six months of adjuvant oxaliplatin-based chemotherapy is standard for patients with stage III colon cancer following surgery. However, oxaliplatin is associated with peripheral neurotoxicity which worsens over treatment duration. Consequently, a shorter treatment duration, if equally effective, would be extremely beneficial. A pooled analysis of data for 12 834 stage III colon cancer patients, from six randomised phase III trials of adjuvant therapy, the International Duration Evaluation of Adjuvant chemotherapy study, was carried out and the results presented at the ASCO Annual Meeting 2017. To clarify the potential impact of these results on clinical practice, ESMO decided to sponsor a special session at their 2017 Annual Meeting dedicated to achieving a more meaningful interpretation of the results. Methods: Medical oncologists from Europe, the United States and Asia selected for their involvement in the trials, together with an independent statistician and an independent clinician, were invited to provide their independent interpretations of the results and contribute to a moderated panel discussion. The pooled analysis evaluated the non-inferiority of 3 versus 6 months of adjuvant FOLFOX/CAPOX therapy but not the non-inferiority of 3 months CAPOX versus 6 months FOLFOX therapy. Results: There was strong evidence of an interaction between the choice of regimen (CAPOX or FOLFOX) and duration of treatment. Patients were classified as either 'fighters' or 'fatalists', and 3-month CAPOX was considered standard for patients classified as fatalists even if they had high-risk disease. However, patients classified as 'fighters' would only receive 3 months of CAPOX if they had low-risk disease but would always receive 6 months of CAPOX/FOLFOX if they had T4 disease. The panel was split on whether they would advocate 3 or 6 months CAPOX therapy based on high-risk N2 disease. Conclusions: The main drivers of the duration of treatment were choice of regimen and patient attitude, with risk, based mainly on T4 stage, having less influence.